Modeling Poliovirus Infection Using Human Engineered Neural Tissue Enriched With Motor Neuron Derived From Embryonic Stem Cells - Cosset, Érika; Hibaoui, Youssef; Ilmjärv, Sten; Dietrich, Pierre-Yves; Tapparel, Caroline; Krause, Karl-Heinz (Frontiers in Cell and Developmental Biology, 2021)
Poliomyelitis is caused by poliovirus (PV), a positive strand non-enveloped virus. Since 1950s, several cell culture methods were developed along with molecular methods to detect and accurately identify PV strains. Here, we provide an accurate and standardized protocol to differentiate human embryonic stem cells towards the neural lineage to generate a motor neuron-enriched engineered neural tissue (mnENT). After confirming the presence of motor neurons (MN), we showed that they are infected by PV-3 at early time points after infection. Moreover, our study revealed the molecular events occurring upon PV-3 infection in the mnENT and highlighted the modulation of a set of genes involved in EGR- EP300 complex. By providing a relevant model able to mimic PV-3 tropism in an exclusively human environment, this study not only describes a protocol to differentiate mnENT but also improves our understanding of PV-3 tropism and the early cellular and molecular events occurring after its infection.